Utilisation of gasification and incineration fly ashes for soft clay stabilisation - Lim, Choon Hock (Nanyang Technological University, 2022)
The aim of this report is to evaluate the potential use of GFA and IFA as supplementary cementitious materials (SCM) with ordinary Portland cement (OPC) to stabilise marine soft clay. The experiments utilised a combination of OPC-GFA and OPC-IFA mix to stabilise the soft clay. The specimens were cured in batches of 28 and 90 days, and measured for water content, dry density, pH, leaching behaviour as well as unconfined compressive strength (UCS). In addition, X-ray diffraction (XRD) was conducted to analyse the mineralogy of the treated marine soft clay. The results indicated that substituting up to 8% OPC with GFA or 6% OPC with IFA produced considerable compressive strength gained with very little heavy metal leaching detected. However greater ranges of blends can be further studied upon.